Mitochondrial Dysfunction and Oxidative Stress in Asthma: Implications for Mitochondria-Targeted Antioxidant Therapeutics - P. Hemachandra Reddy (MDPI AG, 2011)
Asthma is a complex, inflammatory disorder characterized by airflow obstruction of variable degrees, bronchial hyper-responsiveness, and airway inflammation. Asthma is caused by environmental factors and a combination of genetic and environmental stimuli. Genetic studies have revealed that multiple loci are involved in the etiology of asthma. Recent cellular, molecular, and animal-model studies have revealed several cellular events that are involved in the progression of asthma, including: increased Th2 cytokines leading to the recruitment of inflammatory cells to the airway, and an increase in the production of reactive oxygen species and mitochondrial dysfunction in the activated inflammatory cells, leading to tissue injury in the bronchial epithelium. Further, aging and animal model studies have revealed that mitochondrial dysfunction and oxidative stress are involved and play a large role in asthma. Recent studies using experimental allergic asthmatic mouse models and peripheral cells and tissues from asthmatic humans have revealed antioxidants as promising treatments for people with asthma. This article summarizes the latest research findings on the involvement of inflammatory changes, and mitochondrial dysfunction/oxidative stress in the development and progression of asthma. This article also addresses the relationship between aging and age-related immunity in triggering asthma, the antioxidant therapeutic strategies in treating people with asthma.